The mystical elements of politics. The perspective of Simone Wail - Tamošaitytė, Rūta (Politologija, 2018)
[full article and abstract in Lithuanian; abstract in English]The word “mysticism” is known to be a term that is now being used and associated with something which is negative – a mockery. It can be said that this perception of the term is based on certain historical events, when, in the central philosophies of particular religions (in this work, focus will be drawn only on Christian mysticism), a unique shift took place – during the early modernity in most of the Christian Churches, there occurred a split between theology and spirituality. Therefore, everything that had even a slight implication of mysticism was seen as irrelevant and unimportant. In addition to this, it is possible to say that our contemporary era has lost all belief in any reality that surpasses peoples daily tasks. Because of this, the vast majority of postmodernists tend to argue that mysticism can not be part of any philosophy, including a political one.This article concentrates on the thought of Simone Weil, a unique French philosopher and mystic, in order to prove through her work that mysticism can potentially enrich political philosophy. This is being done by analyzing her work and attempting to underline the supernatural element between the human and society. This supernatural element will yield a further investigation of how Simone Weil’s mysticism can affect political philosophy. In order to find this element, the concepts of the human and the society that occur in Simone Weil’s philosophy will be analyzed separately.In the first part, it is analyzed how Simone Weil perceived humans. She drastically separates the human, who, in her thought, possesses a transcendent core that can be violated, from the person, who is illusionary. Meanwhile, the second part concentrates on Weil’s perception of the relation between society and the human. Society is seen by Weil as the Platonic Great Beast, but it may also be a source of pure fulfillment – roots – for the human being. In this part of the study, the roots of a human being in society and the tragedy of uprootedness are discussed further.The third part develops an idea of why mysticism can be seen as an important part of political philosophy and why it should not be neglected: it provides a different angle – a divine one – for viewing people’s daily lives and their culture. Mysticism always comes from a certain culture, and it is important, since a mystic communicates their thought through that culture; however, a mystic also is able to critically address the surrounding culture because of the divine point of view. That is why mysticism is essential for political philosophy.The analization of Weil’s views on obligations, the human transcendental core and roots leads to a conclusion which suggests that the supernatural element between the human and society is an obligation for oneself and for others. This supernatural element allows us to confirm the idea that political philosophy should not neglect the mystical approach.
Keywords: none